2021
DOI: 10.1200/jco.2021.39.15_suppl.1058
|View full text |Cite
|
Sign up to set email alerts
|

AMEERA-1: Phase 1/2 study of amcenestrant (SAR439859), an oral selective estrogen receptor (ER) degrader (SERD), with palbociclib (palbo) in postmenopausal women with ER+/ human epidermal growth factor receptor 2-negative (HER2-) metastatic breast cancer (mBC).

Abstract: 1058 Background: AMEERA-1 (NCT03284957) investigates amcenestrant, an oral SERD, as monotherapy and combined with targeted therapies in ER+/HER2– mBC. Here we report data from dose escalation (Part C) and dose expansion (Part D) of amcenestrant + palbo. Methods: Patients (pts) were postmenopausal women with ER+/HER2– mBC and ≥ 6 mos prior advanced endocrine therapy (ET) or adjuvant (adj) ET resistance (relapse on adj ET started ≥ 24 mos ago or < 12 mos after completing adj ET). Prior chemotherapy (≤ 1) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“… 25 Preliminary results from an ongoing, first-in-human phase 1/2 trial (AMEERA-1) showed that amcenestrant has promising antitumor activity as monotherapy and in combination with the CDK4/6 inhibitor palbociclib and that no clinically significant cardiac or ocular safety findings occurred. 30 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 Preliminary results from an ongoing, first-in-human phase 1/2 trial (AMEERA-1) showed that amcenestrant has promising antitumor activity as monotherapy and in combination with the CDK4/6 inhibitor palbociclib and that no clinically significant cardiac or ocular safety findings occurred. 30 , 37 , 38 …”
Section: Discussionmentioning
confidence: 99%
“… 38 No clinically significant cardiac or ocular safety findings occurred in either set of cohorts. 30 , 38 …”
Section: Introductionmentioning
confidence: 89%
“… 63 An interaction between amcenestrant and palbociclib is possible, with amcenestrant having a moderate cytochrome P450 3A4 induction effect and reducing palbociclib exposure in a dose-dependent manner, hence the recommended dose for amcenestrant is 200 mg in combination with palbociclib, compared with 400 mg as monotherapy. 65 Several oral SERDs are undergoing evaluation in combination with abemaciclib, but no results are reported yet. These include trials of amcenestrant (NCT03284957), camizestrant (NCT03616587 and NCT04964934), imlunestrant (NCT04188548 and NCT04975308) and ZN-c5 (NCT04514159).…”
Section: Oral Serd With Cdk4/6 Inhibitor Early Phase Trialsmentioning
confidence: 99%
“…In the phase I/II AMEERA-1 study, among 59 evaluable patients treated with monotherapy, the ORR was 9% and the CBR was 34%, increasing to 64% among patients without prior SERD, CDK4/6 inhibitors, or mTOR inhibitors [79]. Among 39 patients treated with amcenestrant plus palbociclib, the ORR was 32% and CBR at 24 weeks was 73%, with a median PFS of 15 months (range 11-22.3) [80,81]. The most frequent any-grade toxicities occurring in ≥ 15% of patients were fatigue and nausea; 13% of patients experienced grade ≥ 3 toxicities with amcenestrant alone [79,82].…”
Section: Serds With Basic Amino Side Chainsmentioning
confidence: 99%